DEVELOPMENT OF THE TECHNIQUE OF THE ANALYSIS OF THE FINANCIAL CONDITION OF THE ENTERPRISES TAKING INTO ACCOUNT SPECIFICS OF BRANCH INDUSTRY (AT THE EXAMPLE OF THE ENTERPRISES OF MECHANICAL ENGINEERING INDUSTRY) - I. Krasyukova (Publishing House of the State University of Management, 2016)
The article describes the most common methods of analysis of financial state of enterprises. Advantages and disadvantages of each method have been investigated. The model of financial state analysis of enterprises of machine-building industry has been developed.